Evaluasi Program Pemberian Makanan Tambahan (PMT) Lokal 90 Hari Pada Balita Stunting Di Puskesmas Dayeuhluhur 1 Kabupaten Cilacap - Wahyu Sariningsih; Atika Nur Azizah (2026)
Stunting is a chronic health problem that requires multisectoral intervention. One of the efforts to address this issue is through the provision of local supplementary feeding (PMT) programs. Purpose This study aims to evaluate the implementation of a 90-day local PMT program for stunted toddlers in the working area of Dayeuhluhur 1 Public Health Center, Cilacap Regency. Methode The study employed a qualitative method with a case study approach. Informants included nutrition officers, health cadres, midwives, village officials, and parents of toddlers. Data were collected through in-depth interviews, documentation, and triangulation. Result The findings showed that the program’s input components aligned with local regulations, particularly Cilacap Regent Regulation No. 60 of 2019. Funding was sourced from village funds, implemented by cadres and health workers, using locally available food ingredients. The implementation process was systematic, covering target identification, food distribution, and nutrition education. The program output included target coverage, daily food provision, and positive community response. The outcomes indicated improvements in children's nutritional status and a reduction in stunting rates from 11% to 8%. Challenges such as difficult terrain and food refusal were overcome through adaptive strategies and cross-sectoral coordination.Conclusion The local PMT program is effective in supporting stunting reduction through community-based collaboration.